Operational Aspects of Fiscal Policy in Oil-Producing Countries - Barnett, Steven (IMF Working Papers; Working Paper ;, 2002)
Oil-producing countries face challenges arising from the fact that oil revenue is exhaustible, volatile, and uncertain, and largely originates from abroad. Reflecting these challenges, the paper proposes some important general principles for the formulation and assessment of fiscal policy in these countries. The main findings can be summarized in some key guidelines: the non-oil balance should feature prominently in the formulation of fiscal policy; it should generally be adjusted gradually; the government should strive to accumulate substantial financial assets over the period of oil production; and, where necessary, strategies should aim at breaking procyclical fiscal responses to volatile oil prices.